Gestational Estimated Glomerular Filtration Rate and Adverse Maternofetal Outcomes - Sehoon Park; Seung Mi Lee; Joong Shin Park; Joon-Seok Hong; Ho Jun Chin; Ki Young Na; Dong Ki Kim; Kook-Hwan Oh; Kwon Wook Joo; Yon Su Kim; Hajeong Lee (Karger Publishers, 2018)
Background/Aims: The association between gestational estimated glomerular filtration rate (eGFR) and adverse pregnancy outcomes has not been fully investigated. Methods: This observational cohort study included pregnancy cases of singleton mothers whose serum creatinine levels were measured during pregnancy at two tertiary hospitals in Korea from 2000 to 2015. Those with identified substantial renal function impairment (eGFR < 60 mL/min/1.73 m2 at baseline, during, or after pregnancy) were excluded. The Chronic Kidney Disease Epidemiology Collaboration equation was used for the eGFR calculation. We computed the time-averaged eGFR during gestation to determine representative values when there were multiple measurements. We studied the following three gestational complications: preterm birth (< 37 weeks' gestational age), low birth weight (< 2.5 kg), and preeclampsia. Results: Among the 12,899 studied pregnancies, 4,360 cases experienced one or more gestational complications. The adjusted odds ratio (aOR) and 95% confidence interval of composite gestational complications for eGFR ranges other than the reference range of 120-150 mL/ min/1.73m2 were: ≥150 mL/min/1.73m2, aOR 1.64 (1.38-1.95), P< 0.001; 90-120 mL/min/1.73m2, aOR 1.41 (1.28-1.56), P< 0.001; and 60-90 mL/min/1.73m2, aOR 2.56 (1.70-3.84), P< 0.001. Incidence of preterm birth or low birth weight showed similar U-shaped association with eGFR values; otherwise, preeclampsia or small for gestational age occurred more often in mothers with a lower gestational eGFR than in those with a higher value. Conclusion: Considering the unique association between gestational eGFR and pregnancy outcomes, carefully interpreting these results may help predict obstetric complications.